KEMAMPUAN PEMECAHAN MASALAH SISWA DALAM MENYELESAIKAN SOAL HOTS (HIGHER ORDER THINKING SKILLS) - Sholiha, Lailatus; Widayanti , Evi (Universitas Insan Budi Utomo, 2023)
This study aims to describe students' problem-solving abilities in solving HOTS questions for class XII MIPA MA Miftahul Ulum students on SPLTV material. The method used in this study is a qualitative descriptive method. After the research subjects have completed the problems given by the researchers, namely HOTS questions, the researchers will describe the results of these solutions based on indicators of problem-solving ability, namely 1) problem identification, 2) settlement planning. problem, 3) implementing the settlement plan, 4) and checking again. The research subjects taken were based on scores taken from the Odd Semester Final Assessment for the 2021-2022 academic year. The results of this study are that students' problem solving abilities are still relatively low because almost all students can only do two stages of problem solving, namely the stage of problem identification and implementation of a problem solving plan. Students still have difficulty in carrying out the planning stage of problem solving and the stage of checking again.